2019
DOI: 10.1111/nmo.13545
|View full text |Cite
|
Sign up to set email alerts
|

Fecal urgency is common in constipated patients and is associated with anxiety

Abstract: Background Fecal urgency is a symptom generally associated with diarrhea but is also reported by patients with constipation. Our aim was to (a) assess the prevalence and burden of fecal urgency in constipated patients (b) evaluate gastrointestinal and psychiatric predictors of moderate to severe fecal urgency in these patients. Methods Patients presenting consecutively to a tertiary outpatient gastroenterology clinic with constipation were included. Patients were considered to have moderate to severe fecal urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a recent study on IBS-C, about 71% of patients reported faecal urgency. Like urge to move of typical RLS, urge to defaecate is associated with the unpleasant sensation (pain or bloating) in the abdomen 19. Mangel et al define faecal urgency as ‘unpleasant sensation that one needs to rush to the toilet or they may soil themselves’.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on IBS-C, about 71% of patients reported faecal urgency. Like urge to move of typical RLS, urge to defaecate is associated with the unpleasant sensation (pain or bloating) in the abdomen 19. Mangel et al define faecal urgency as ‘unpleasant sensation that one needs to rush to the toilet or they may soil themselves’.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the patients with digestive system dysfunction had a signi cantly higher anxiety and depression rate than those without digestive system complications. Studies have found that constipation and diarrhea often aggravate the anxiety of patients, and anxiety may affect the course of the disease through the neuroendocrine regulatory system, further aggravating the clinical symptoms of patients and exacerbating constipation [31,32]. A study on Parkinson's disease (PD) patients showed that severe constipation and motor symptoms were closely related to depression; the researchers explained that involvement of the enteric plexus of the gastrointestinal tract and dorsal motor nucleus of the vagus (DMV) initially causes constipation in PD patients, and subsequent spread to the raphe nuclei and locus coeruleus leads to depressive mood [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the patients with digestive system dysfunction had a significantly higher anxiety and depression rate than those without digestive system complications. Studies have found that constipation and diarrhea often aggravate the anxiety of patients, and anxiety may affect the course of the disease through the neuroendocrine regulatory system, further aggravating the clinical symptoms of patients and exacerbating constipation [31,32]. A study on Parkinson's disease (PD) patients showed that severe constipation and motor symptoms were closely related to depression; the researchers explained that involvement of the enteric plexus of the gastrointestinal tract and dorsal motor nucleus of the vagus (DMV) initially causes constipation in PD patients, and subsequent spread to the raphe nuclei and locus coeruleus leads to depressive mood [33].…”
Section: Discussionmentioning
confidence: 99%